Factors Influencing the Interfacial Bonding Characteristics Between Cold Patching Asphalt Mixture and the Old Pavement - Chen, Fengchen; Liu, Kaidi; Tan, Yiqiu; Ye, Song; Xu, Huining; Ouyang, Jian (Frontiers in Materials, 2020)
Cold Patching Asphalt Mixture(CPAM) has been widely used in pothole repair due to the advantages of convenient construction and easy storage. However, CPAM usually has a short service life because of insufficient bonding to the old pavement during service. Therefore, in order to ensure the good bonding of CPAM to the old pavement and improve the integrity and durability of pothole repair, this work carried out a study on the influencing factors of the bonding characteristics between CPAM to the old pavement. The oblique shear test was used as the research method with an evaluating index shearing strength. Influencing factors which affect the interface bonding characteristics, such as temperature, humidity, types of tack coat, the amount of tack coat spreading and surface roughness, were compared and analyzed. The analysis results illustrated that the interface bonding characteristics are weak at high temperature and decreases with the increase of humidity. There exists an optimal binder spreading amount where the denser CPAM is, the smaller the spreading amount of the tack coat is. The groove on the old pavement can increase the bond strength of the interface, but there is an optimal groove spacing. Based on this, the gray correlation analysis method was used to clarify the influence degree of various factors and reveal the dominant factors affecting the interface bonding characteristics. The analysis indicated that the dominant influencing factors of the interface bonding characteristics are the type of tack coat and the roughness of the surface.